Mobile Payments, Demographics and Firm Performance in Kenya - Njenga, Adrian Kamotho; Litondo, Kate; Mwabu, Germano (European Scientific Journal, ESJ, 2021)
Technological advancements have presented firms with an opportunity to use mobile payments to enhance their performance. This study explores the relationship between mobile payments and firm performance in Kenya. The moderating effects of demographics are also studied. Using primary data collected from 289 supermarkets based in Nairobi City County, we determine whether the use of mobile payment has enhanced firm performance as defined by profitability, operation costs, revenues and the number of customers served. Empirical results from logit regression analysis reveal that the use of a mobile to make payments in supermarkets directly impacts the performance of supermarkets. Additionally, consumer characteristics have a significant moderating effect on the relationship between mobile payments and profitability of supermarkets. We conclude that the use of mobiles to make payments in supermarkets in Kenya has acquired the requisite critical mass level to be in a position to influence revenues of these firms.